UBL3 modification influences protein sorting to small extracellular vesicles - Hiroshi Ageta (Nature Portfolio, 2018)
Exosomes mediate cell-to-cell communication by transporting proteins, mRNAs, and miRNAs but the mechanisms of protein sorting to exosomes are poorly understood. Here, the authors uncover that ubiquitin-like 3 (UBL3) regulates protein sorting to exosomes by acting as a posttranslational modification.